Dimenzije učiteljevega profesionalnega razvoja - Makovec Radovan, Danijela (Sodobna pedagogika, 2018)
The article examines the conceptions of the role of teachers in planning and conducting instruction. The thesis that teachers perform several roles in their work is generally established. However, an in-depth investigation reveals that different researchers have addressed this matter from different perspectives. The first part of the article presents the conceptions of the role of teachers in Slovenia and abroad. We conclude that answers to the question about the qualities of good teachers and the roles they (should) perform cannot be found in a simple set of desired qualities or competences expected of teachers. The issue should be approached through multiple layers and wider contexts (the environment, the school subject, years of service, etc.). The second part of the article presents the findings of a research study conducted in 16 Slovenian grammar schools in which the teachers confirmed our preliminary thesis that, in their work, they occupy several roles that are necessarily intertwined. The article also presents seven dimensions of the role of teachers that were identified by the participating teachers as crucial for their work.
Keywords: didactic excellence; education; izobraževanje učiteljev; pedagogical excellence; profesionalni razvoj; strokovna usposobljenost; subject excellence; teachers; the role of teachers; učitelji; vzgoja in izobraževanje